Modelling of edge crack formation and propagation in ceramic laminates using the stress–energy coupled criterion. (November 2016) - Ševeček, Oldřich; Kotoul, Michal; Leguillon, Dominique; Martin, Eric; Bermejo, Raul
Abstract: The high compressive stresses in ceramic laminates utilized to enhance their fracture resistance may lead to the formation of edge cracks at the surface of the compressive layers. In this work, a 2D parametric numerical model is developed to assess the effect of residual stress and thickness of the compressive layers on the edge crack formation, by using a coupled stress–energy criterion. The results predict the existence of a lower bound, below which no edge crack occurs (i.e. obtaining crack-free laminates), and an upper bound, beyond which onset of the edge crack would lead to the complete delamination of the compressive layer.